2000
DOI: 10.1046/j.1537-2995.2000.40091111.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood as a source of autologous RBCs for transfusion to preterm infants

Abstract: The preparation of autologous RBCs from the CB of preterm infants is technically possible in principle. However, major concerns must be raised as to whether such preparations are of benefit in ensuring safe care of neonates with blood components, with respect to the high rate of bacterial contamination and the limited availability in babies with low birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
86
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 10 publications
(14 reference statements)
3
86
0
1
Order By: Relevance
“…Autologous blood transfusions have been shown to be safe in both adult and pediatric patients (17,21,25). Umbilical/placental cord blood is autologous blood from a neonate (20), and the use of autologous umbilical cord blood (UCB) has long been discussed among neonatologists (5,6,9,10,29). Owing to the increasing utilization of UCB for the transplantation of hematopoietic stem cells, significant progress has been made in developing safer and more efficient collection techniques for UCB (12,14).…”
mentioning
confidence: 99%
“…Autologous blood transfusions have been shown to be safe in both adult and pediatric patients (17,21,25). Umbilical/placental cord blood is autologous blood from a neonate (20), and the use of autologous umbilical cord blood (UCB) has long been discussed among neonatologists (5,6,9,10,29). Owing to the increasing utilization of UCB for the transplantation of hematopoietic stem cells, significant progress has been made in developing safer and more efficient collection techniques for UCB (12,14).…”
mentioning
confidence: 99%
“…Approximately 20 mL of CB/kg of body weight can be recovered, and a linear association has been found between collected CB volume and birth weight, with a greater relative CB volume from placentas of smaller newborns. 30 Correspondingly, we could collect a mean volume of 20 mL/kg of body weight for infants younger than 28 weeks of gestational age, although a linear correlation between the collected CB volume and birth weight or gestational age was not identified. These results are similar to those obtained by Brune and associates, who collected approximately 20 mL of CB/kg of body weight, irrespective of birth weight.…”
Section: Discussionmentioning
confidence: 92%
“…Umbilical cord blood (UCB) has been suggested as a source for autologous transfusions 1,5,6 . Placental vessels contain a quarter to a third of the newborn blood volume, and the fetal blood left in the placental vessels may serve as a source of autologous blood 7,8 .…”
mentioning
confidence: 99%
“…Placental vessels contain a quarter to a third of the newborn blood volume, and the fetal blood left in the placental vessels may serve as a source of autologous blood 7,8 . Although studies have shown that the collection and the storage of UCB are feasible for transfusion in newborn infants, the use of UCB for transfusion in preterm infants is reported in few studies 5,[8][9][10][11][12] . We previously tested the safety and feasibility of the collection and storage method of the autologous blood 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation